Cardiovascular Diseases in India Compared With the United States - Prabhakaran, Dorairaj; Singh, Kavita; Roth, Gregory A; Banerjee, Amitava; Pagidipati, Neha J; Huffman, Mark D (Journal of the American College of Cardiology, 2018)
This review describes trends in the burden of cardiovascular diseases (CVDs) and risk factors in India compared with the United States; provides potential explanations for these differences; and describes strategies to improve cardiovascular health behaviors, systems, and policies in India. The prevalence of CVD in India has risen over the past 2 decades due to population growth, aging, and a stable age-adjusted CVD mortality rate. Over the same time period, the United States has experienced an overall decline in age-adjusted CVD mortality, although the trend has begun to plateau. These improvements in CVD mortality in the United States are largely due to favorable population-level risk factor trends, specifically with regard to tobacco use, cholesterol, and blood pressure, although improvements in secondary prevention and acute care have also contributed. To realize similar gains in reducing premature death and disability from CVD, India needs to implement population-level policies while strengthening and integrating its local, regional, and national health systems. Achieving universal health coverage that includes financial risk protection should remain a goal to help all Indians realize their right to health.